2008
DOI: 10.1177/0363546508322903
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic versus Mini-Open Rotator Cuff Repair

Abstract: Based on current literature, there was no difference in outcomes between the arthroscopic and mini-open rotator cuff repair techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 38 publications
1
74
1
5
Order By: Relevance
“…Debates continued throughout the 1990s, comparing open versus arthroscopic rotator cuff repair [9,28,30,48,49,59,62]. The millennium ushered in a new brand of surgeons who, during their residencies, made the transition to arthroscopic shoulder surgery [10,19,38,42]. Arthroscopic surgery reportedly provides similar functional scores, pain relief, clinical tests of motion and strength, and patient satisfaction to open rotator cuff repair [28,30,38,42,44,49,55,59,62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debates continued throughout the 1990s, comparing open versus arthroscopic rotator cuff repair [9,28,30,48,49,59,62]. The millennium ushered in a new brand of surgeons who, during their residencies, made the transition to arthroscopic shoulder surgery [10,19,38,42]. Arthroscopic surgery reportedly provides similar functional scores, pain relief, clinical tests of motion and strength, and patient satisfaction to open rotator cuff repair [28,30,38,42,44,49,55,59,62].…”
Section: Introductionmentioning
confidence: 99%
“…The millennium ushered in a new brand of surgeons who, during their residencies, made the transition to arthroscopic shoulder surgery [10,19,38,42]. Arthroscopic surgery reportedly provides similar functional scores, pain relief, clinical tests of motion and strength, and patient satisfaction to open rotator cuff repair [28,30,38,42,44,49,55,59,62]. Two recent reviews of the arthroscopic and mini-open rotator cuff repair literature reported that both techniques resulted in similar UCLA scores, mean ASES scores, patient satisfaction ratings, complications, active elevation, and active external rotation [38,42].…”
Section: Introductionmentioning
confidence: 99%
“…25,[33][34][35][36][37][38] We found that, at 5 years post-surgery, the arthroscopic knotless technique produced greater strength in external rotation than both open and arthroscopic knotted repairs, and was the only technique to show a significant increase in the rotator cuff functional index compared to pre-operative level. Between the pre-operative examination and 5-year follow-up, the open repair group did not improve in any plane of shoulder strength measurement except lift off, whereas both arthroscopic knotted and arthroscopic knotless repairs improved in all modes of strength except adduction; corresponding with its purpose as the examinations internal control.…”
Section: Discussionmentioning
confidence: 71%
“…9,13,14 83 to 92% of arthroscopic cuff repairs achieve satisfactory results. [14][15][16][17][18][19] Techniques using staples or suture anchors in single or double rows have been described, 5,7,[20][21][22][23][24] but few reported on tendon-cuff integrity after arthroscopic repair. 25 Metal implants can lead to complications, especially in patients with chronic rotator cuff tears, poor-quality bone in the greater tuberosity, and articular damage caused by a loose or intra-articular metal anchor.…”
Section: Discussionmentioning
confidence: 99%